THE RADICALISM OF YOUNG PEOPLE IN INDONESIA THE RELIGIOUS PORTRAITS OF ISLAMIC SPIRITUAL ORGANIZATIONS - Jaetul Muchlis (UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. Youth, radicalism, and intolerance are serious problems that continue to develop and become a discourse in Indonesia and other countries, including the Middle East. In recent years, the emergence of symptoms of radicalism and intolerance among young people has increased. The tendency to increase the interest of Muslim youth to join organizations or religious groups that are intolerant also contributes to the significant increase in the symptoms of radicalism. Symptoms that appear make them have an intolerant and extremist attitude that leads to violence. Data from the research results and deepening of the BNPT strengthen this phenomenon. In Indonesia, some of the perpetrators of acts of terrorism are still young. They were about 23-27 years old with a lack of religious understanding. Even the movement mode of radical groups targeting young people is mainly concentrated in educational institutions at the junior high school and senior high school levels, even at the university level, such as Islamic spiritual youth group (Rohis). among students. Various kinds of religious upheaval are often related to social change and the things that accompany it, including social unrest, mobility, and conflict. The theme of religious radicalism is undoubtedly not new. However, the author assumed that the composition of radicalism remains essential, and needs to be developed continuously by all generations. The study written in this paper will explore the phenomenon of young people and the behavior of radicalism and intolerance in educational institutions such as Rohis (Intelorance in the Rohis literature) and society in general.Abstrak. Pemuda, radikalisme, dan intoleransi adalah masalah serius yang hingga kini terus berkembang dan menjadi diskursus di Indonesia dan negara-negara lain termasuk di Timur Tengah. Fenomena munculnya gejala radikalisme dan intoleransi di kalangan kaum muda dalam beberapa tahun terakhir ini meningkat. Kecenderungan peningkatan minat kaum muda Islam bergabung dalam organisasi-organisasi atau kelompok-kelompok keagamaan yang terindikasikan intoleran turut mensuplai besarnya peningkatan gejala radikalisme. Gejala yang muncul menjadikan mereka memiliki sikap intoleran dan ekstrimis yang mengarah pada tindakan kekerasan. Data dari hasil penelitian dan pendalaman BNPT memperkuat fenomena tersebut, dewasa ini di negara Indonesia sebagian pelaku aksi terorisme diketahui berusia muda, berada di rentang usia kisaran 23-27 tahun dengan pemahaman keagamaan yang rendah. Bahkan modus pergerakan kelompok radikal dengan sasaran kaum muda banyak terkonsentrasi di lembaga-lembaga pendidikan tingkat Sekolah Menengah Pertama maupun Sekolah Mengah Atas bahkan sampai ke tingkat perguruan tinggi seperti Rohis, misalnya berdasarkan hasil survei Lembaga Kajian Islam dan Perdamaian (LaKIP) menunjukan adanya faham konservatisme keagamaan di kalangan Siswa. Berbagai macam pergolakan keagamaan pun sering dijumpai berkaitan dengan perubahan sosial dengan hal-hal yang menyertainya, termasuk di dalamnya keresahan sosial, mobilitas, dan pertikaian. Tema radikalisme paham keagamaan tentu bukan merupakan tema baru, namun demikian penulis berasumsi bahwa tema radikalisme tetap penting dan perlu dikembangkan secara terus-menerus oleh banyak orang atau penulis dari semua generasi. Pada pengkajian yang ditulis dalam makalah ini akan mengeksplor fenomena kaum muda serta perilaku radikalisme dan intoleransi di Lembaga Pendidikan seperti Rohis (Inteloransi dalam literatur Rohis) dan di masyarakat secara umum.